Enhanced NLO and antibacterial properties of nicotinic acid-doped KDP crystals: synthesis, growth and characterisation. (23rd February 2017) - Deepa, B.; Philominathan, P.
Abstract : A biocompatible non-linear optical crystals (458 × 7 mm) of nicotinic acid-doped potassium dihydrogen phosphate (KDP) were grown by the slow evaporation technique at room temperature and their structural study was confirmed by single-crystal X-ray diffraction. Further, the presence of functional groups and elements were verified using Fourier transform infra-red and Energy dispersive X-ray studies. The optical properties of these crystals such as transmission and absorption were analysed by Ultra Violet Visible Near infra-red spectroscopy and the second harmonic generation efficiency was carried out by the Kurtz–Perry powder technique. The mechanical properties of the grown crystal were studied using Vickers' hardness tester. The grown crystals were involved in an antibacterial activity against certain potentially threatening microbes such as Bacillus subtilis, Escherichia coli, Staphylococcus aureu and Klebsiella pneumoniae . The dopant efficiently screened the bacteria than that of the pure KDP crystal.